Islamic Education in Addressing Modern Challenges: A Modern Tafsir Perspective of Quraish Shihab - Harun Arrasyid Ar-Rasyid; M. Rizky Luftiansyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study examines the concept of Islamic education in addressing the challenges of modern life through the modern Qur’anic interpretation of M. Quraish Shihab. The study aims to explore Shihab’s understanding of education and identify its relevance to the moral, spiritual, intellectual, and social challenges faced by contemporary society. This study employs a qualitative library research approach by examining Quraish Shihab’s works, particularly Tafsir Al-Mishbah, together with relevant literature on Islamic education and Qur’anic interpretation. The analysis focuses on educational principles, objectives, methods, and their relevance to contemporary educational needs. The findings indicate that Shihab views Islamic education as a comprehensive process grounded in the Qur’an and directed toward the development of the whole human being, encompassing physical, spiritual, and intellectual dimensions. Education is not limited to the transfer of knowledge but also involves purification of the soul, moral formation, and the development of human responsibility as a servant and vicegerent of Allah. Several educational approaches, including exemplary conduct, dialogue, and mujahadah, are relevant to contemporary education. Shihab’s interpretation of Q.S. Al-‘Alaq 1–5 further emphasizes reading, learning, intellectual responsibility, and the transmission of knowledge. The study concludes that Quraish Shihab’s modern interpretive approach provides a contextual and holistic foundation for Islamic education to respond to modern challenges while maintaining Qur’anic values and strengthening faith, knowledge, and noble character.